RESPON PERTUMBUHAN VEGETATIF TANAMAN JAGUNG MANIS (Zea mays saccharata Sturt.) TERHADAP DOSIS PUPUK ORGANIK DAN PUPUK KALIUM - Sugito Loso; Haris Kriswantoro (University of Prof. Dr. Hazairin, SH, 2025)
This study aimed to determine the effect of manure type and KCl fertilizer dosage on the vegetative growth of sweet corn plants. The research was conducted in R Rejosari Village, Tugumulyo District, Musi Rawas Regency, from June to August 2024. This study used a Factorial Randomized Block Design (FRBD) consisting of 2 treatment factors and repeated 3 times. The observation data were analyzed using Analysis of Varians (ANOVA) using the R Studio program. f the results of the analysis of variance test are significantly tested at the 5% level, and if the results of the analysis of variance test are very significantly tested at 1%. then it will be continued with the honest significant difference test (HSD). The treatments that will be applied are as follows: The first treatment is the type of manure (M) which consists of 3 types of levels, namely: M1 = Cow Manure Dose 1 kg, M2 = Goat Manure Dose 1 kg, M3 = Chicken Manure Dose 1 kg. The dose of potassium fertilizer (M) consists of 3 types of levels, namely: P1 = Dose 5 g / polybag, P2 = Dose 7.5 g / polybag, P3 = Dose 10 g / polybag. Chicken manure has the best effect on plant height, number of leaves per plant, stem diameter, wet biomass weight, and dry biomass weight of plants